Replicate and evaluate the results of peptic ulcer perforation score in our setup as a predictor of mortality following a peptic ulcer perforation - Patel, Jimitkumar; Chaudhari, Sandipkumar; Chaudhari, Sonalben (International Journal of Research in Medical Sciences, 2022)
Background: Scores commonly employed to risk stratify perforated peptic ulcer patients include ASA (American Society of Anesthesiologists), Boey and peptic ulcer perforation score (PULP). Accurate and early identification of high-risk surgical patients with a perforated peptic ulcer is important for triage and risk stratification. The objective of the present study was to replicate and re-evaluate the results of this score in our setup, compared to the cohort study carried out in Denmark. Method: A prospective study was conducted on 40 surgically treated patients for peptic ulcer perforation for period of one year. There was no age restriction. The predefined outcome measure was mortality within 30 days of surgical procedure for peptic ulcer perforation. Different Variables used are age, co-morbid disease, liver cirrhosis, steroids use, shock on admission, the time lapse between perforation and admission, serum creatinine, as well as ASA score 2 to 5. Results: A total of 40 patients were studied in a single hospital over one year. Nearly 12.5% (5 patients) died within 30 days of surgery. Out of total deaths, most deaths occurred in patients with a PULP score of more than 7, and the risk of mortality increases with an increase in the PULP score. So, the risk stratification is classified into low risk and high risk according to pulp score. Conclusions: The PULP score can be used to predict 30-day mortality in patients with peptic ulcer perforation who have undergone surgery almost accurately and thus assist in risk stratification and triage. This study hence replicates the cohort study in Denmark in our setup.